Personalized social networking: An applied scenario in a portable personality environment - Reymann, S.; Alves, D.; Lugmayr, Artur (2008)
in today?s world digital communication is about connecting people and bridging communities globally. Social networking as today?s buzz word is the keyword for this trend. Facebook or MySpace are just the beginning of possible other emerging tools for social networking in the digital era. Starting with a simple messenger to chat with friends to the creation of a complex ancestry circle of your relatives using a family tree tool, social networking services increasingly accompany us integrating ourselves into our communities. The next generation of tools will let new opportunities emerge - "personalized communication integrating existing social network platforms.? Within the scope of this paper we present an application scenario of the open source platform Portable Personality (P2). Using the P2 Model we are able to collect social network characteristics from multiple messenger services and merge them into one shared personal space. A representative profile flows in a shared and distributive network to contemplable consumer applications providing personalized services based on social interdependencies. Copyright 2008 ACM.